(untitled) (Journal of Engineering, 2003)
This paper reports the conversion of a large unsignalised roundabout (HURIYA SQUARI!) relatively close to the University of Baghdad campus to a signalized intersection. The study focused on reduction of vehicle delay and queue length at this intersection area. During the course of this research project, two software packages for the analysis and design of isolated intersection, SIDRA (Akcelik, R.1986 and 1991) and HCS (Transportation Research Board, National Research Council 1994) were available. A trial site selected and the observed dara used in the evaluation of the SIDRA and HCS outputs. The evaluation process indicated that SIDRA produce vehicle delay, which is reasonably consistent with the observed vehicle delay. Hence, SIDRA software used in the evaluation of alternative designs of the HURIYA SQUARE intersection. Five proposals of signaling plans and four proposed geometric layouts examined. The first proposal evaluated on site; the other four proposals examined with aid of the SIDRA software. Based on the carried analysis, the intersection geometric layout, signal timing, and phasing plan which result in lower vehicle delay and higher reserved capacity selected. The Local Authority (AMANAT BAHGDAD) adopted the selected design and the large roundabout converted to a signalized intersection. Observation of traffic behavior following the conversion indicates a considerable improvement in traffic movement performance